First experimental demonstration of forced dynamic aperture measurements with LHC ac dipoles - F. S. Carlier; R. Tomás; E. H. Maclean; T. H. B. Persson (Physical Review Accelerators and Beams, 2019)
Diagnostics of nonlinear beam dynamics has become more important for the LHC as it advances into increasingly challenging regimes of operation, as well as for the High Luminosity LHC where machine nonlinearities will have a significantly larger impact. Limitations of traditional excitation methods at top energy, in particular due to machine protection, have pushed the development of safe alternative methods using ac dipoles to characterize the nonlinear content of the LHC. One of the methods that has been proposed is the dynamic aperture under forced oscillation of ac dipoles. This new observable has the potential to help characterize relative changes in the nonlinear content of the machine, improve the understanding of the nonlinear models by comparing to simulations, validate nonlinear optics corrections, and give a qualitative lower bound estimate on the free dynamic aperture. This paper presents the first experimental demonstration of forced dynamic aperture measurements under forced oscillations performed using the LHC ac dipoles, and discusses the benefits of forced dynamic aperture measurements in circular colliders.